Hubungan Karakteristik dan Lingkungan Belajar Klinik dengan Kecemasan Mahasiswa Saat Praktek Klinik di Rsjd Dr Amino Gondohutomo Semarang - Iswanti, Dwi Indah; Suratih, Kanthi; Winasti, Wenni (Jurnal Keperawatan Jiwa, 2015)
Nursing students often experience anxiety during studying nursing including current clinicalpractice. Students experience new situations and circumstances in the hospital environment, but it is a source ofanxiety is when the students are required to provide nursing actions to patients (Helena 2003, dalam Anggelina2012). Purpose: The purpose of this study was to determine the correlation of student characteristics andclinical learning environment toward the current anxiety clinical practice in Dr. Amino Gondohutomo RSJSemarang. Methods: This research method is a kind of analytical research with correlational cross-sectionalapproach. The number of respondents in this study was 92 people with proportional stratified random sampling.And the analysis technique Chi Square test. Results: The results of the chi square test between age and anxietylevel obtained chi square value of 18.411 (p = 0.000 <0.05), chi square test results between the sexes withanxiety levels obtained chi square value of 12.151 (p = 0.002 <0.05) , chi square test results between educationand anxiety levels obtained chi square value of 15.866 (p = 0.000 <0.05), chi square test results betweenclinical learning environment with a level of anxiety obtained chi square value of 54.672 (p = 0.000 <0, 05).Conclusion: There was a relationship between age, sexes, the level of education at the time of the students'anxiety, and there was a correlation between the clinical learning environment on students' anxiety in clinicalpractice in Dr. RSJD. Amino Gondohutomo Semarang